ETIKA BERKOMUNIKASI: MENGHINDARI BAHAYA GHIBAH DENGAN BIJAK MENURUT IMAM NAWAWI - Larasati, Zu'ama Anggun; Afifah, Umi; Ghani, Ainal; Cahaya Kesuma, Guntur; Amirudin (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Ghibah (backbiting) is a form of negative communication strongly condemned in Islam due to its harmful impact on both individual spirituality and social harmony. This study explores the concept of ghibah based on the views of Imam Nawawi, who in his works Riyadhus Shalihin and Al-Adzkar emphasizes that ghibah is a major sin—even when the information conveyed is true. Using a qualitative approach through library research, this paper analyzes the definition, Qur’anic and Hadith evidence, forms, consequences, and preventive strategies related to ghibah. Imam Nawawi offers practical solutions such as controlling the tongue, avoiding toxic environments, practicing positive thinking, and increasing remembrance of God and good deeds. Ghibah not only deteriorates individual character and interpersonal trust, but also leads to spiritual bankruptcy in the afterlife. This research underscores the importance of ethical speech as an essential part of faith and a foundation for fostering a just and harmonious Islamic society.